2019
DOI: 10.1021/acs.est.9b02226
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Pet Tags Associate Tris(1,3-dichloro-2-isopropyl) Phosphate Exposures with Feline Hyperthyroidism

Abstract: Feline hyperthyroidism is the most commonly diagnosed endocrine-related disease among senior and geriatric housecats, but the causes remain unknown. Exposure to endocrine-disrupting compounds with thyroid targets, such as flame retardants (FRs), may contribute to disease development. Silicone passive sampling devices, or pet tags, quantitatively assessed the bioavailable FR exposures of 78 cats (≥7 y) in New York and Oregon using gas chromatography–mass spectrometry. Pet tags were analyzed for 36 polybrominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 70 publications
0
32
0
Order By: Relevance
“…When asked if they were seeing health issues in feral cats suspected of being caused by exposures to toxins or environmental contaminants, 13.8% respondents reported yes, 59.0% of reported no, and 27.2% reported that it was unknown (n = 544). In categorizing write-in explanations, the common trends for those reporting a concern were chemical or toxic exposures (51), infectious diseases (10), climate and weather related issues (5), reproductive issues and birth defects (4), suspected cancers and carcinogens (4), and firearms (3). Some respondents suspected observing health issues in feral cats caused by environmental exposures, with the intentional poisoning of cats as the most commonly-mentioned problem.…”
Section: Environmental Human and Public Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…When asked if they were seeing health issues in feral cats suspected of being caused by exposures to toxins or environmental contaminants, 13.8% respondents reported yes, 59.0% of reported no, and 27.2% reported that it was unknown (n = 544). In categorizing write-in explanations, the common trends for those reporting a concern were chemical or toxic exposures (51), infectious diseases (10), climate and weather related issues (5), reproductive issues and birth defects (4), suspected cancers and carcinogens (4), and firearms (3). Some respondents suspected observing health issues in feral cats caused by environmental exposures, with the intentional poisoning of cats as the most commonly-mentioned problem.…”
Section: Environmental Human and Public Healthmentioning
confidence: 99%
“…A vast majority had not (90.2%), and some were unsure (5.6%) or reported yes (4.2%) (n = 449). By grouping the write-in answers for those who had sought help, the 2 most common type of entities contacted were veterinarians and academics (6) and cat welfare organizations (5), and the only motivating needs mentioned by more than 1 group were planning their spay/neuter programs (2) and quantifying cats (2). Inversely, we also asked if a group had ever been contacted by an academic or researcher who wanted to work with them or collect data about their organization.…”
Section: Data and Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…To prevent adverse health outcomes, it is useful to investigate what factors contribute to higher pEDC exposures. Previous literature has examined both environment- and participant-based factors associated with higher chemical exposures ( Dixon et al, 2019 ; Fent et al, 2017 ; Fent et al, 2018 ; Gibson et al, 2019 ; Poutasse et al, 2019 ; Poutasse et al, 2020 ; Reddam et al, 2020 ). For instance, urinary flame retardant metabolite concentrations decrease with increased hand washing and house cleaning ( Gibson et al, 2019 ); and concentrations of the flame retardant tris(1,3-dichloro-2-isopropyl) phosphate increase with longer driving commutes ( Reddam et al, 2020 ) and more time spent on upholstered furniture ( Poutasse et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%